Overlapping mRNA transcripts of photosynthesis gene operons in Rhodobacter capsulatus. - Wellington, C L (1991)
The crtEF, bchCA, and puf operons of the facultative phototrophic bacterium Rhodobacter capsulatus encode gene products that are necessary for the formation of various components of the photosynthetic apparatus. The crtEF operon encodes two enzymes involved in the biosynthesis of carotenoids, the bchCA operon codes for two enzymes of the bacteriochlorophyll biosynthetic pathway, and the puf operon encodes four pigment-binding polypeptides as well as two polypeptides with less well understood functions. These three operons are adjacent to one another on the chromosome and are transcribed in the same direction. We present the results of RNA blotting and S1 nuclease protection end-mapping experiments which provide direct evidence that the mRNA transcripts of these three operons overlap. Therefore, it is likely that the crtEF, bchCA, and puf operons can be expressed as a single transcriptional unit, although RNA polymerase may initiate transcription at any of several promoters.